The Efficacy of Three Species of Trichodew for the control of Basal Stem Rot in Oil Palm Seedlings - Nagappan, Jayanthi (2005)
This study evaluated the potential of three Trichoderma species, namely T. harzianum t (isolate BIO T32), T. longibrachiatum (BIO T28) and T. virens (BIO T128) for the control of Ganoderma boninense (EGB Ol), the causal pathogen of basal stem rot (BSR) of oil palms in nursery trials. Besides their spore production and antagonistic properties, h s study also investigated the growth response of each of the species towards a wide range of temperature and pH conditions. All three species exhibited particular strengths in the growth parameters studied but BIO T32 exhibited consistent and relatively good antagonistic properties and was used as the main inoculant in 'nursery trials against G. boninense. The type and size of wood block were found to influence the success and consistency of the inocula in establishing disease during artificial infection of seedlings. Very low infectivity rates were acheved when inoculum blocks were half to a quarter of the standard 6 x 6 x 12 cm; this size was found to give consistent infection rates leading to approximately 85% mortality. In nursery trials, seedlings treated with a single inoculum of T. lzarzianum (TI) gave the lowest and most significant disease severity index (DSI) of 28.34. The conidial drench was stopped at week 14 and the first sign of disease was only observed on week 20. The uninfected and untreated control seedlings gave a DSI of 0 where as, the infected, untreated controls gave a DSI of 86.87. Soils under treatment using a single (TI), two mixed (T2) and three mixed (T3) inocula showed an increase in spore count based on colony forming units (cfu) starting from two weeks after application. When the soil drench was tenninated at week 14, the spore count was peak on the 18&, 1 4 a~nd 1 0 ~ week for TI, T2 and T3 treatments respectively. Spore counts of BIO T32 were not significantly different on the upper (5 cm) and deeper (15 cm) layer of the treated soils. This study found that when T. lzarzianum (BTO T32) was used as a single inoculum, it f gave the most significant and effective performance as a biological control agent. This was only followed by a mixture of T. hurzianum and T. longibrachiatum. Lastly, the use of a combination of three Trichoderma species were found to give the poorest disease control, giving a DSI that was not statistically different from the infected, untreated control experiment.